Comparative Analysis Of Regulation And Supervision Of Islamic Banking Between Malaysia And Gambia - Mohd Faisol Ibrahim; Nik Mohd Fadhil Nik Mohammad; Musa Manjang (Universiti Malaysia Sabah, 2024)
Non-Indexed Publication